2019
DOI: 10.1038/s41467-019-08334-7
|View full text |Cite
|
Sign up to set email alerts
|

Usp7 regulates Hippo pathway through deubiquitinating the transcriptional coactivator Yorkie

Abstract: The Hippo pathway plays an important role in organ development and adult tissue homeostasis, and its deregulation has been implicated in many cancers. The Hippo signaling relies on a core kinase cascade culminating in phosphorylation of the transcription coactivator Yorkie (Yki). Although Yki is the key effector of Hippo pathway, the regulation of its protein stability is still unclear. Here, we show that Hippo pathway attenuates the binding of a ubiquitin-specific protease Usp7 to Yki, which regulates Hippo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 63 publications
1
60
0
Order By: Relevance
“…In our data, most upstream members of the Hippo signaling pathway showed a trend toward downregulation and these genes were negatively regulated by primarily upregulated miR-NAs, especially the muscle-specific miRNAs miR-1a-3p, miR-206-3p, and miR-133a/b. Moreover, previous studies showed that the activity of Yap1 and Wwtr1 was negatively regulated by the upstream regulatory elements of the Hippo signaling pathway 36,52 . In summary, the differentially expressed miRNAs altered the abundance of Hippo pathway members.…”
Section: Discussionmentioning
confidence: 99%
“…In our data, most upstream members of the Hippo signaling pathway showed a trend toward downregulation and these genes were negatively regulated by primarily upregulated miR-NAs, especially the muscle-specific miRNAs miR-1a-3p, miR-206-3p, and miR-133a/b. Moreover, previous studies showed that the activity of Yap1 and Wwtr1 was negatively regulated by the upstream regulatory elements of the Hippo signaling pathway 36,52 . In summary, the differentially expressed miRNAs altered the abundance of Hippo pathway members.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various types of posttranslational modifications (PTMs) including dephosphorylation (Huang et al, 2013; Liu et al, 2013; Wang et al, 2012; Wilson et al, 2014), ubiquitination (Cho et al, 2020; Sun et al, 2019; Yao et al, 2018), methylation (Fang et al, 2018; Oudhoff et al, 2013), and O-GlcNAcylation (Peng et al, 2017; Zhang et al, 2017) that have been implicated in fine-tuning YAP activity, phosphorylation is regarded as a dominant manner of YAP regulation. The classic Hippo-YAP signaling features sequential phosphorylation of YAP at Ser127 (Zhang et al, 2008, 2015; Zhao et al, 2007) and Ser381/Ser384 (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…About 40 wing discs were lysed in TRIzol (Invitrogen) for RNA isolation according to previous described [ 54 ]. One microgram RNA was used for reverse transcription by HiScript ® Q RT SuperMix with gDNA wiper (Vazyme) according to the instructions.…”
Section: Methodsmentioning
confidence: 99%